Preparation and application of fluorescent probe capable of continuously identifying cations and HPO42-
By loading and functional NZVI/NI dual metal clusters on NA-X boiler, the problem of easy gathering and oxidation of nano metal clusters is solved, and a fluorescent probe with high stability and anti-interference capabilities has been achieved. Effective identification and detection of cations and anion.
Patent Information
- Application Number
- CN202311548311.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-20
- Publication Date
- 2025-01-21
AI Technical Summary
Nano-metal clusters are prone to aggregation and oxidation, affecting their fluorescence intensity, and the existing technology cannot effectively solve this problem.
By loading NZVI/NI dual metal clusters on NA-X boiler, and surface functionalization, including aminoization modification and aldehydes dehydrated contraction response to prepare a fluorescent probe with high stability and anti-interference ability.
Significantly enhances the stability of nZVI/Ni binary metal clusters, reduces agglomeration, improves the ability to identify cations and anions, and produces color changes visible to the naked eye under ultraviolet light.
Smart Images

Figure CN119331604A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fluorescent materials, and in particular to a method for continuously identifying cations and HPO4 2- Preparation and application of fluorescent probes. Background Art
[0002] Nanometal clusters are particles containing a small number (<40) of metal atoms. Due to their special structural size, they have excellent fluorescence properties. Compared with quantum dots, nanometal clusters have higher optical stability. nZVI (nano-zero-valent iron) is currently mainly used in soil and water remediation due to its excellent performance in decontamination and low cost-effectiveness. There are two methods for the synthesis of nZVI: top-down and bottom-up. In the former, large-scale materials are converted into nZVI with the help of mechanical and chemical processes such as milling and etching. The latter method is based on chemical synthesis, self-assembly, etc., and grows into nanostructures atom by atom or molecule by molecule. Both methods involve the use of reducing agents to reduce and precipitate nZVI from aqueous iron salts. At present, the main research areas of nZVI include: (1) synthesis and reactivity of nZVI; (2) transport in porous media; (3) aggregation; (4) polymer modification, etc. nZVI / Ni (nano-zero-valent iron nickel) binary metal clusters are mainly used in activation degradation and soil remediation.
[0003] In addition, in the prior art, CN 110628042 A discloses a fluorescence-enhanced metal nanocluster / zeolite imidazolate skeleton composite nanomaterial, which is based on the principle of aggregation-induced emission and quantum confinement effect. The prepared metal nanocluster / zeolite imidazolate skeleton composite material can enhance the luminescence performance of metal nanoclusters and is applied to the field of cell imaging. The composite material can alleviate the aggregation of nZVI / Ni to a certain extent, but cannot solve the oxidation resistance of nZVI / Ni.
[0004] Since nanometal clusters are prone to aggregation and oxidation, which affects their fluorescence intensity, how to further optimize the stability of nanometal clusters and develop new applications for nanometal clusters has become a technical problem that needs to be solved in this field. Summary of the invention
[0005] In view of this, the present invention is proposed.
[0006] In a first aspect, the present invention provides a method for preparing a fluorescent probe, comprising:
[0007] (1) Using Na-X zeolite as a carrier, nZVI / Ni binary metal clusters were loaded on the surface of Na-X zeolite using an iron source, a nickel source, and a reducing agent to prepare the fluorescent probe P1;
[0008] (2) reacting the fluorescent probe P1 with a compound containing an amino group to obtain the fluorescent probe P2;
[0009] (3) The fluorescent probe P2 is subjected to a dehydration condensation reaction with a compound containing an aldehyde group to obtain a fluorescent probe.
[0010] The present invention finds through screening of a large number of carriers that Na-X zeolite is selected as a carrier, which can well load nZVI / Ni binary metal clusters, so that the stability of the nZVI / Ni binary metal clusters is greatly enhanced, and the occurrence of agglomeration can be effectively reduced; moreover, the present invention finds that the nZVI / Ni binary metal clusters loaded on the Na-X zeolite can simultaneously identify cations and anions, and have good stability and anti-interference ability.
[0011] However, the nZVI / Ni binary metal clusters loaded on Na-X zeolite will still undergo oxidation, thereby affecting the ion recognition performance. Therefore, the present invention further discovered, through a large number of screening attempts to introduce surfactant groups, that by first performing amino modification on the surface and then undergoing a dehydration condensation reaction with aldehyde groups, the surface functionalized fluorescent probe obtained not only has high stability, but the introduced surface functionalized groups will not affect the ion recognition performance.
[0012] In addition, the introduced surface functionalized groups are conjugated systems, which can greatly promote the red shift of the fluorescence detection wavelength, so that the prepared fluorescent probe produces colors visible to the naked eye under ultraviolet light and produces different colors when identifying different ions.
[0013] In some embodiments, the compound containing an aldehyde group is salicylaldehyde; and the compound containing an amino group is ethylenediamine.
[0014] In some embodiments, Na-X zeolite is prepared using microwave hydrothermal synthesis.
[0015] In some embodiments, the step of preparing Na-X zeolite by microwave hydrothermal synthesis comprises:
[0016] (1) dissolving Na2SiO3 and NaAlO2 in alkaline solutions respectively to prepare Na2SiO3 solutions and NaAlO2 solutions;
[0017] (2) Na2SiO3 solution was added dropwise to NaAlO2 solution, and after microwave reaction at 85-95°C, the solid was separated to obtain Na-X zeolite.
[0018] The present invention further discovered that the microwave hydrothermal synthesis method can not only significantly reduce the synthesis time, but also control the particle size distribution and surface morphology of the Na-X zeolite, which is more conducive to the uniform dispersion loading of the nZVI / Ni binary metal clusters on its surface, thereby improving the stability of the prepared fluorescent probe.
[0019] Preferably, the amounts of Na2SiO3 and NaAlO2 are calculated based on a molar ratio of Si to Al of 1:(0.8-1.2).
[0020] Preferably, after the Na2SiO3 solution is added dropwise to the NaAlO2 solution, the mixture is stirred for more than 20 minutes, subjected to microwave reaction at 85-95°C, and then the solid is separated by centrifugation to obtain the Na-X zeolite.
[0021] In some embodiments, the preparation method of the fluorescent probe, step (1) comprises:
[0022] An aqueous solution containing an iron source, a nickel source and PEG is mixed with Na-X zeolite to prepare a first mixture; and an aqueous solution containing a reducing agent and concentrated hydrochloric acid is dripped into the first mixture under an inert atmosphere to prepare a fluorescent probe P1.
[0023] Preferably, the reducing agent is Vc and NaI.
[0024] Preferably, the inert atmosphere is N2.
[0025] In a second aspect, the present invention provides a fluorescent probe prepared by the preparation method in any of the above schemes.
[0026] In a third aspect, the present invention provides a reagent or a kit, which contains a fluorescent probe prepared by any of the above schemes.
[0027] In a fourth aspect, the present invention further provides the use of the fluorescent probe, reagent or kit prepared by any of the above schemes in the detection of cations and / or anions.
[0028] In some embodiments, the fluorescent probe, reagent, or kit detects cations and anions simultaneously.
[0029] In some embodiments, the cation is Zn 2+ 、Al 3+ Mg 2+ At least one of; and / or, the anion is HPO4 2- .
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention provides a fluorescent probe which has excellent stability and anti-interference ability, can detect and identify cations and anions at the same time, and produces color changes visible to the naked eye under ultraviolet light, and has very broad application prospects in the field of ion recognition and detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the XRD characterization diagram of Na-X zeolite.
[0033] Figure 2 This is the FT-IR characterization diagram of Na-X zeolite.
[0034] Figure 3 This is a schematic diagram of the synthetic route of fluorescent probe P3.
[0035] Figure 4 is the XRD pattern of the fluorescent probe.
[0036] Figure 5 is the XRD pattern of the fluorescent probe.
[0037] Figure 6 It is the FT-IR spectrum of the fluorescent probe.
[0038] Figure 7 It is the scanning electron micrograph of fluorescent probes P1, P2 and P3.
[0039] Figure 8 The fluorescent probe P3 recognizes Zn 2+ Fluorescence spectrum of .
[0040] Fig. 9 The fluorescent probe P3 recognizes Al 3+ Fluorescence spectrum of .
[0041] Fig.10 The fluorescent probe P3 in THF recognizes Mg 2+ Fluorescence spectrum of .
[0042] Fig.11 The fluorescent probe P3 in DMF recognizes Mg 2+ Fluorescence spectrum of .
[0043] Fig.12 The fluorescent probe P3 in DMSO recognizes Mg 2+ Fluorescence spectrum of .
[0044] Fig.13 The coexistence of other cations has an adverse effect on Zn 2+ Resulting graph of identified interference.
[0045] Fig.14 The coexistence of other cations has an effect on Al 3+ Resulting graph of identified interference.
[0046] Fig.15 Is the coexistence of other cations to Mg 2+ Resulting graph of identified interference.
[0047] Fig.16 The probe P3 and Zn in EtOH 2+ Fluorescence titration spectrum of .
[0048] Fig.17 The probe P3 in EtOH detects Zn 2+ Linear relationship results graph.
[0049] Fig.18 The probe P3 and Al in DMAC 3+ Fluorescence titration spectrum of .
[0050] Fig.19 It is the probe P3 in DMAC that detects Al 3+ Linear relationship results graph.
[0051] Fig. 20 The probe P3 and Mg in THF 2+ Fluorescence titration spectrum of .
[0052] Fig.21 Probe P3 in THF detects Mg 2+ Linear relationship results graph.
[0053] Fig. 22 The probe P3 and Mg in DMF 2+ Fluorescence titration spectrum of .
[0054] Fig.23 Probe P3 in DMF detects Mg 2+ Linear relationship results graph.
[0055] Fig.24 The probe P3 and Mg in DMSO 2+ Fluorescence titration spectrum of .
[0056] Fig.25 The probe P3 in DMSO detects Mg 2+ Linear relationship results graph.
[0057] Fig.26 The probe P3 in EtOH is 2+ Fluorescence spectrum changes under the alternating action of EDTA.
[0058] Fig. 27 The probe P3 in DMSO is 2+ Fluorescence spectrum changes under the alternating action of EDTA.
[0059] Fig.28 The probe P3 in DMAC is 3+ Fluorescence spectrum changes under the alternating action of EDTA.
[0060] Fig.29 This is a diagram showing the mechanism of action of probe P3 in recognizing metal ions.
[0061] Fig.30 It is the probe P3+Mg in DMSO 2+ Fluorescence spectrum changes when reacting with various anions.
[0062] Fig.31 Is the coexistence of other anions to HPO4 2- Resulting graph of identified interference.
[0063] Fig.32 It is the probe P3+Mg in DMSO 2+ With HPO4 2- Fluorescence titration spectra.
[0064] Fig.33 It is the probe P3+Mg in DMSO 2+ Fluorescence intensity at 458 and 480 nm and HPO4 2- Linear relationship diagram.
[0065] Fig.34 It is the probe P3+HPO4 in DMSO 2- Fluorescence spectra. DETAILED DESCRIPTION
[0066] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0067] If no specific techniques or conditions are specified in the examples, all are carried out according to conventional methods or the techniques or conditions described in the literature in the field, or according to the product instructions. If no manufacturer is specified for the reagents and instruments used, all are conventional products that can be purchased through regular channels.
[0068] The X-ray diffractometer was TD-3700 from Dandong Tongda Technology Co., Ltd.;
[0069] The fluorescence spectrophotometer was F-2710 from Shimadzu Enterprise Management Co., Ltd.;
[0070] The infrared spectrometer is LR64912C from Bojin Elmer Instrument Co., Ltd.
[0071] The drugs and reagents used in the following examples are all analytically pure. The solvents are anhydrous ethanol, tetrahydrofuran (THF), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), and dimethyl sulfoxide (DMSO). The masking agent is ethylenediaminetetraacetic acid (EDTA).
[0072] The cation is Ag + 、Al 3+ , Ba 2+ , Ca 2+ 、Cd 2+ 、Co 2+ Cr 3+ , Cu 2+ , Fe 3+ , Hg 2+ , K + Mg 2+ , Mn 2+ 、Ni 2+ , Pb 2+ 、Zn 2+ 、Zr 4+ , a total of 17 species, including Ba 2+ , Ca 2+ 、Ni 2+ As hydrochloride, Mg 2+ , Mn 2+ , Pb 2+ 、Zn 2+ is acetate and the rest are nitrates.
[0073] The anion is HSO3 - 、SO3 2- 、SO4 2- 、S2O3 2- 、SCN - , HS - , S 2- 、NO2 - ,I - 、AlO2 - 、CH3COO - , Cl - 、HCO3 - PO4 3- 、HPO4 2- , a total of 15 types, all of which are sodium salts.
[0074] The above ions were prepared with deionized water to a concentration of 1.0*10 -2 mol / L solution was used as the analyte solution.
[0075] Example 1
[0076] This embodiment provides a method for preparing a fluorescent probe, the steps are as follows:
[0077] 1. Synthesis of Na-X zeolite
[0078] Take 5.34g NaOH and dissolve it in 50mL deionized water. The solution was divided into two parts. One part was used to dissolve 2.42g NaAlO2 and the other part was used to dissolve 8.39g Na2SiO3﹒9H2O. The molar ratio of Si / Al was 1:1. The Na2SiO3 solution was then slowly added dropwise to the NaAlO2 solution. After magnetic stirring for 30min, the solution was subjected to microwave reaction at 90℃ for 3h. After centrifugation, the supernatant was removed and the solid was dried in a drying oven to obtain Na-X zeolite (S2 sample).
[0079] The XRD characterization diagram of Na-X zeolite is shown in Figure 1 As shown, sharp and clear diffraction peaks appear at 2θ positions of 7.20°, 10.18°, 12.48°, 16.13°, 21.70°, 24.02°, 26.17°, 27.12°, 29.98°, and 34.28°, and the zeolite is confirmed to be Na-X with reference to the standard XRD spectrum of Na-X zeolite.
[0080] The FT-IR characterization results of Na-X zeolite are shown in Figure 2 As shown in the figure, the functional groups present in Na-X zeolite were analyzed by referring to the standard FT-IR spectrum of Na-X zeolite. -1 The sharpest absorption peak at the Al-O and Si-O tetrahedrons is as (asymmetric stretching vibration) at 666cm -1 and 723cm -1 The absorption peaks appearing at υ s (symmetric stretching vibration) related, 3524cm -1 and 1652cm -1 The absorption peaks that appear are respectively related to the υ as , δ s (bending vibration). The results show that the prepared Na-X zeolite sample contains [SiO4] 4- and [AlO4] 5- Tetrahedral structure. At the same time, because the sample had been infrared dried before infrared spectrum detection, the characteristic absorption peak of -OH still appeared, indicating that Na-X zeolite may contain -OH structure.
[0081] 2. Synthesis of fluorescent probes
[0082] Take 1g FeCl3﹒6H2O, 0.8794g NiCl2﹒6H2O, 1g PEG (polyethylene glycol) and dissolve them in 50mL deionized water. After the solution is clarified, add 1g of the Na-X zeolite prepared above and transfer it to a 100mL three-necked flask. Take 3g ascorbic acid and 5mg NaI and dissolve them in 20mL deionized water. Add 2-3 drops of concentrated hydrochloric acid, stir evenly and transfer to a constant pressure funnel. After the experimental device is assembled, N2 is introduced. After 5-10 minutes, when the air in the device is exhausted, open the knob of the constant pressure funnel to make the liquid drop rate 2-3 drops / second, and react for 3h at room temperature with magnetic stirring. After the reaction is completed, centrifuge the solid and dry it in a vacuum drying oven for use. Dilute the mother liquor 15,000 times with deionized water to obtain the fluorescent probe P1 solution.
[0083] Take 1g FeCl3﹒6H2O, 0.8794g NiCl2﹒6H2O, 1g PEG (polyethylene glycol) and dissolve them in 50mL deionized water. After the solution is clarified, add 1g of the Na-X zeolite prepared above and transfer it to a 100mL three-necked flask. Take 3g ascorbic acid and 5mg NaI and dissolve them in 20mL deionized water. Add 2-3 drops of concentrated hydrochloric acid and stir evenly before transferring to a constant pressure funnel. After the experimental device is assembled, N2 is introduced. After 5-10 minutes, when the air in the device is exhausted, turn on the knob of the constant pressure funnel to make the liquid drop rate 2-3 drops / second. After the ascorbic acid and NaI solutions are added, stir the reaction under magnetic stirring at room temperature for 0.5h, then slowly add 6mL ethylenediamine with a constant pressure dropping funnel. After the addition is complete, continue stirring at room temperature for 2.5h. After the reaction is completed, centrifuge the solid and dry it in a vacuum drying oven to obtain the fluorescent probe P2 solid.
[0084] Take 2 mL of salicylaldehyde and dissolve it in 10 mL of anhydrous ethanol. After fully mixing, add 0.5 g of fluorescent probe P2 solid and react under magnetic stirring at room temperature for 10 hours. After the reaction is completed, centrifuge the mother liquor after centrifugation and dilute it 100 times with anhydrous ethanol to obtain the fluorescent probe P3 solution.
[0085] Schematic diagram of the synthetic route of fluorescent probe P3 Figure 3 shown.
[0086] The XRD pattern of the fluorescent probe is as follows Figure 4 and Figure 5As shown, S2 is a zeolite sample, and probe P1 has new diffraction peaks at 2θ of 31.81°, 45.56°, 57.60°, and 61.23°, but no characteristic diffraction peaks of Na-X zeolite appear. Referring to the standard spectrum of nZVI / NiXRD, it is known that 45.56° and 57.60° correspond to the diffraction peak positions of nZVI / Ni, and 31.81° and 61.23° correspond to the diffraction peak positions of Fe2O3 and NiO, respectively. The results show that nZVI / Ni binary metal clusters have been loaded on the surface of zeolite Na-X, but nZVI / Ni has been partially oxidized. As the reaction proceeds, part of nZVI / Ni is consumed, exposing part of the zeolite, causing probes P2 and P3 to present diffraction peaks similar to those of Na-X zeolite, but with weaker peak intensities. The 2θ positions were selected as 45.58°, 24.03°, and 24.03°, respectively, and the average particle sizes of probes P1 to P3 were calculated to be 0.998nm, 1.030nm, and 1.194nm, respectively.
[0087] The FT-IR spectrum of the fluorescent probe is as follows Figure 6 As shown, S2 is a zeolite sample. Referring to the nZVI FT-IR spectrum, probes P1 to P3 are at 656 cm -1 A weak absorption peak appears at s(Fe-O) About, at 1636cm -1 、3468cm -1 The absorption peaks at δ s(H-O) ,υ as(H-O) Probes P2 and P3 at 1383 cm -1 The absorption peak at δ s(C-H) The characteristic absorption peak of -NH2 in probe P2 may be covered by the absorption peak of -OH and is not apparent. -1 、2898cm -1 The absorption peaks at as(C-H) ,υ s(C-H) About, at 2372cm -1 The absorption peak at 756 cm-1 may be related to the accumulated double bonds of CO2 in the air. -1 The weak absorption peak at 1630 cm -1 The absorption peak at δ s(H-O) ,υ s(C=N) This indicates that probe P3 contains a Schiff base structure.
[0088] SEM images of P1, P2 and P3 are shown in Figure 7 As shown, P1, P2 and P3 are the upper left picture, the upper right picture and the lower picture respectively. It can be seen that P1 and P2 are layered stacking structures, while P3 forms a spatial network structure; the particles of the three are all about 5μm.
[0089] Example 2
[0090] This example tests the ion recognition performance of the fluorescent probe P3 prepared in Example 1. The fluorescence detection excitation wavelength of the fluorescent probe P3 in all solvents is 350nm, except for Zn 2+ The detection limit experiment was carried out under the detection condition of a slit width of 10 nm, and the other related experiments were carried out under the detection condition of a slit width of 5 nm.
[0091] (I) Fluorescence recognition of cations
[0092] The detection method is as follows:
[0093] Take 2 mL of solvent in a cuvette, add 20 μL of P3 fluorescent probe solution, stir and mix thoroughly, perform fluorescence spectrum detection, and obtain the fluorescence spectrum of the fluorescent probe in the solvent. Then add 2 μL (final concentration of 1*10 -5 mol / L) cation solution, stir and mix thoroughly, make it react completely, and then perform fluorescence spectrum detection again to obtain the fluorescence spectrum of the fluorescent probe + cation. Use the same operation method to detect the fluorescence spectra of the fluorescent probe + other metal ions in turn.
[0094] 1. Identification of Zn by fluorescence spectroscopy 2+
[0095] The results are as follows Figure 8 As shown, the probe P3 solution in the ethanol phase is em The fluorescence intensity at 438 nm was weak. 2+ After that, the fluorescence emission wavelength of the solution red-shifted to 446 nm, and the fluorescence intensity increased by 4.9 times. 3+ Mg 2+ After that, the fluorescence intensity increased by 2.3 and 2.0 times, respectively, while the other 14 cations (Ag + , Ba 2+ , Ca 2+ 、Cd 2+ 、Co 2+ Cr 3+ , Cu 2+ , Fe 3+ , Hg 2+ , K + , Mn 2+ 、Ni 2+ , Pb 2+ 、Zr 4+ ) has little or no effect on its fluorescence intensity.
[0096] Therefore, the probe P3 has a strong affinity for Zn in the ethanol phase. 2+It has a good identification effect. When the probe P3 solution is irradiated with 365nm light from a portable ultraviolet lamp, it can be observed that the probe P3 solution and the probe P3+Zn 2+ The solution colors are clearly different ( Figure 8 The fluorescence of the solution changes from weak fluorescence to deep blue fluorescence.
[0097] 2. Identification of Al by fluorescence spectroscopy 3+
[0098] The results are as follows Fig. 9 As shown, the probe P3 solution in DMAC is em The fluorescence intensity at 434 nm was weak. 3 + After that, the fluorescence emission wavelength of the solution red-shifted to 458nm, the solution fluorescence changed from weak fluorescence to blue-green fluorescence, and the fluorescence intensity increased by 8.6 times. 2+ Mg 2+ After that, the fluorescence intensity increased by 3.4 and 3.8 times, respectively, while the other 14 cations had little or no effect on their fluorescence intensity. 3+ It has better identification function.
[0099] 3. Identification of Mg by fluorescence spectroscopy 2+
[0100] When THF is selected as solvent, the results are as follows Fig.10 As shown, the probe P3 solution in THF was em The fluorescence intensity at 428 nm was weak. 2+ After the addition of MgCl2, the fluorescence emission wavelength of the solution red-shifted to 440 nm, the solution fluorescence changed from weak fluorescence to blue fluorescence, and the fluorescence intensity increased by 2.8 times, while the other 16 cations had little or no effect on its fluorescence intensity. 2+ It has better identification function.
[0101] When DMF is selected as solvent, the result is as follows Fig.11 As shown, the probe P3 solution in DMF was added with Mg 2+ After that, the solution is at λ em The fluorescence intensity at 455 nm was stronger, the solution fluorescence changed from weak fluorescence to bright blue fluorescence, and the fluorescence intensity increased by 41.3 times. 2+ Its fluorescence intensity increased by 9.4 times, while the other 15 cations had little or no effect on its fluorescence intensity. 2+ Has good identification function.
[0102] When DMSO is selected as solvent, the results are as follows Fig.12 As shown, the probe P3 solution in DMSO was 2+ After that, the solution is at λ em The fluorescence intensity of the solution changed from weak fluorescence to bright blue fluorescence, and the fluorescence intensity increased by 73.2 times. When the same concentration of Zn was added 2+ Its fluorescence intensity increased by 17.3 times after MgCl2 addition, while the other 15 cations had little or no effect on its fluorescence intensity. 2+ It has a good identification function.
[0103] (II) Anti-interference ability detection
[0104] The detection method is as follows:
[0105] Take 2 mL of solvent in a cuvette, add 20 μL of P3 fluorescent probe solution, stir and mix thoroughly, perform fluorescence spectrum detection, and obtain the fluorescence spectrum of the fluorescent probe in the solvent. Then add 2 μL (final concentration of 1*10 -5 mol / L) cation solution, stir and mix thoroughly, make it react completely, and then perform fluorescence spectrum detection again to obtain the fluorescence spectrum of fluorescent probe + cation. Add 2μL (final concentration is 1*10 -5 mol / L) other cationic solutions, stir and mix thoroughly, and detect the fluorescence spectrum of the fluorescent probe + the cationic solution to be tested + other metal ions.
[0106] 1. Effect of other cations on Zn 2+ Identify interference
[0107] like Fig.13 As shown, probe P3 + other cations + Zn 2+ With probe P3+Zn 2+ The fluorescence intensity comparison at 446nm shows that except for Cu 2+ In addition, it significantly reduced the fluorescence intensity of the solution, while the presence of other cations had an effect on the fluorescence of probe P3 and Zn 2+ The effect was small or almost unaffected. Therefore, in EtOH, the probe P3 and Zn 2+ The function of the switch is to have good anti-interference performance.
[0108] 2. Effect of other cations on Al 3+ Identify interference
[0109] like Fig.14 As shown, probe P3+other cations+Al 3+ With probe P3+Al 3+ The fluorescence intensity at 458 nm shows that Co 2+ , Cu 2+The presence of cations can significantly reduce the fluorescence intensity of the solution, while the presence of most other cations can slightly reduce the fluorescence intensity of the solution. Therefore, in DMAC, the probe P3 and Al 3+ The function of the switch is to have good anti-interference performance.
[0110] 3. Effect of other cations on Mg 2+ Identify interference
[0111] like Fig.15 As shown, in DMSO, Cu 2+ The effect on the fluorescence intensity of the solution is small, and the influence of other cations on it can also be ignored. Therefore, in DMSO, the probe P3 and Mg 2+ The function of the product is to have good anti-interference performance.
[0112] (III) Detection limit test
[0113] The detection method is as follows:
[0114] Take 2mL of solvent in a cuvette, add 20μL of fluorescent probe solution, and use the cation accumulation method to make 1.0*10 -2 The cumulative injection volumes of the mol / L cationic solution were 1 μL, 3 μL, 5 μL, 7 μL, 9 μL, 11 μL, 13 μL, 15 μL, and 17 μL, respectively. After each addition of the cationic solution, the mixture was fully stirred and then fluorescence spectrum detection was performed.
[0115] 1. Determination of Zn by fluorescence spectroscopy 2+ Detection limit
[0116] Probe P3 and Zn in EtOH 2+ The fluorescence titration spectrum of Fig.16 As shown, Zn 2+ The concentration is the horizontal axis, and the fluorescence intensity of the solution at 446nm is the vertical axis. -5 mol / L~5*10 -5 mol / L range, with the increase of Zn 2+ As the concentration increases, the fluorescence intensity of the solution increases linearly ( Fig.17 ). Among them, R 2 The linear fitting degree of the detection limit is 0.9876, indicating that the detection limit has a good linear fitting degree and high credibility. According to the detection limit calculation formula LOD = 3δ / k, the detection limit of probe P3 in EtOH for Zn 2+ LOD = 1.562*10 -7 mol / L.
[0117] 2. Determination of Al by fluorescence spectroscopy 3+ Detection limit
[0118] Probe P3 and Al in DMAC 3+ The fluorescence titration spectrum of Fig.18 As shown, in DMAC, Al 3+ The concentration is 5*10 - 7 mol / L~6*10 -6 mol / L range, the fluorescence intensity of the solution at 458nm is similar to that of Al 3+ The concentration showed a good linear relationship ( Fig.19 , R 2 =0.9932), where probe P3 is 3+ LOD = 1.7694*10 -8 mol / L.
[0119] 3. Determination of Mg by fluorescence spectrometry 2+ Detection limit
[0120] Probe P3 and Mg in THF 2+ The fluorescence titration spectrum of Fig. 20 As shown, in THF, Mg 2+ The concentration is 1.0*10 - 6 mol / L~2.1*10 -5 mol / L range ( Fig.21 ), the fluorescence intensity of the solution at 440nm is similar to that of Mg 2+ The concentration showed a good linear relationship (R 2 =0.9971), where probe P3 is positive for Mg 2+ LOD = 1.6197*10 -9 mol / L.
[0121] Probe P3 and Mg in DMF 2+ The fluorescence titration spectrum of Fig. 22 As shown, in DMF, Mg 2+ The concentration is 5.0*10 - 7 mol / L~2.2*10 -5 mol / L range ( Fig.23 ), the fluorescence intensity of the solution at 455nm is similar to that of Mg 2+ The concentration showed a good linear relationship (R 2 =0.9986), where probe P3 is positive for Mg 2+ LOD = 1.9163*10 -9 mol / L.
[0122] Probe P3 and Mg in DMSO 2+ The fluorescence titration spectrum of Fig.24As shown, DMSO, Mg 2+ The concentration is 4.50*10 - 7 mol / L~1.45*10 -5 mol / L range ( Fig.25 ), the fluorescence intensity of the solution at 458 nm is similar to that of Mg 2+ The concentration showed a good linear relationship (R 2 =0.9970), where probe P3 is positive for Mg 2+ The LOD is 1.3390*10 -9 mol / L. Comparing the detection limits in THF and DMF, it can be seen that in DMSO, probe P3 has a low detection limit for Mg 2+ The recognition sensitivity is the highest.
[0123] (IV) Fluorescence spectroscopy study of probe P3 and Zn 2+ Mg 2+ 、Al 3+ Mechanism of action
[0124] Take 2 mL of anhydrous ethanol in a cuvette, add 20 μL of probe P3 solution, 2 μL of Zn 2+ Solution, 1μL 1.0*10 -2 mol / L EDTA solution, 2μL Zn 2+ After each addition of the solution, the solution was fully stirred and mixed, and fluorescence spectra were detected to analyze the activity of probe P3 in Zn 2+ The fluorescence spectrum of probe P3 was analyzed by alternating the action of Mg and EDTA. 2+ Under the alternating action of EDTA, Al 3+ Changes in fluorescence spectrum under the alternating action of EDTA.
[0125] Probe P3 in Zn 2+ The fluorescence spectrum changes under the alternating action of EDTA are as follows Fig.26 As shown, probe P3 in DMSO was 2+ The fluorescence spectrum changes under the alternating action of EDTA are as follows Fig. 27 As shown, probe P3 in DMAC is in Al 3+ The fluorescence spectrum changes under the alternating action of EDTA are as follows Fig.28 shown.
[0126] As can be seen from the figure, after adding EDTA, the probe P3+ metal cation (M n+) The fluorescence intensity of the solution decreased significantly, which may be due to the strong coordination effect of EDTA, which dissociated the metal ions and destroyed the rigid six-membered ring structure formed by probe P3 and metal ions, resulting in a decrease in the fluorescence intensity of the solution. After the metal ions were added again, the six-membered ring structure was restored and the fluorescence intensity of the solution increased again. Therefore, it is preliminarily speculated that the possible mechanism of the probe P3 in recognizing metal ions is Fig.29 shown.
[0127] (V) Fluorescence recognition of anions
[0128] 1. Fluorescence identification of HPO4 2- Anion performance
[0129] The detection method is the same as above, the probe P3+Mg in DMSO 2+ The fluorescence spectrum changes when interacting with various anions are as follows Fig.30 As shown, in DMSO, the probe P3+Mg 2+ Add 5*10 -5 mol / L HPO4 2- After that, the solution λ em The solution fluorescence changes from bright blue to light green, and the fluorescence intensity decreases by 4.1 times. When the same concentration of PO4 is added, 3- , its λ em The red shift is to 468 nm, while the remaining 13 anions (HSO3 - 、SO3 2- 、SO4 2- 、S2O3 2- 、SCN - , HS - , S 2- 、NO2 - ,I - 、AlO2 - 、CH3COO - , Cl - 、HCO3 - ) can slightly increase or decrease the fluorescence intensity of the solution, but it has no identification significance.
[0130] Therefore, in DMSO, the probe P3+Mg 2+ HPO4 2- Has good identification function.
[0131] 2. Effect of other anions on HPO4 2- Identify interference
[0132] The detection method is the same as above, and the results are as follows Fig.31 As shown, by the probe P3+Mg 2+ +Other anions+HPO42- With probe P3+Mg 2 + +HPO4 2- The fluorescence intensity at 480nm shows that HCO3 - ,Ac - , S 2- The presence of can enhance the fluorescence intensity of the solution, while the presence of other anions can enhance the fluorescence intensity of the probe P3+Mg 2+ With HPO4 2- The effect is minor.
[0133] Therefore, in DMSO, the probe P3+Mg 2+ With HPO4 2- The function of the switch is to have good anti-interference performance.
[0134] 3. Determination of HPO4 by fluorescence spectroscopy 2- Detection limit
[0135] The detection method is the same as above, and the results are as follows Fig.32 and Fig.33 As shown, in DMSO, at 1.0*10 -6 mol / L~3.4*10 -5 mol / L range, with HPO4 2- The fluorescence intensity of the solution at 458 nm gradually decreased and reached 7.90*10 -5 mol / L~1.65*10 -4 mol / L range, with HPO4 2- The fluorescence intensity of the solution at 480nm gradually increased. Within the two ranges, the fluorescence intensity was 2- There is a good linear relationship between the two concentrations, R 2 They are 0.9939 and 0.9925 respectively, and the LOD is 7.6809*10 -9 mol / L、4.9929*10 -8 mol / L.
[0136] Probe P3+HPO4 in DMSO 2- Fluorescence spectra such as Fig.34 As shown, by comparing the probe P3+HPO4 2- Solution and probe P3+Mg 2+ +HPO4 2- The emission peak position of the solution is speculated to be due to the new emission peak at 480nm. 2- The increase in concentration, HPO4 2- First, the Mg coordinated with probe P3 2+dissociate, resulting in a decrease in the fluorescence intensity of the solution at 458 nm. 2+ After complete dissociation, it directly interacts with probe P3, resulting in a new emission peak at 480 nm.
[0137] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a fluorescent probe, characterized in that: include: (1) Using Na-X zeolite as a carrier, nZVI / Ni binary metal clusters were loaded on the surface of Na-X zeolite using an iron source, a nickel source, and a reducing agent to prepare the fluorescent probe P1; (2) reacting the fluorescent probe P1 with a compound containing an amino group to obtain the fluorescent probe P2; (3) The fluorescent probe P2 is subjected to a dehydration condensation reaction with a compound containing an aldehyde group to obtain a fluorescent probe.
2. The preparation method according to claim 1, characterized in that: The compound containing aldehyde group is salicylaldehyde; the compound containing amino group is ethylenediamine.
3. The preparation method according to claim 1, characterized in that: Na-X zeolite was prepared by microwave hydrothermal synthesis.
4. The preparation method according to claim 3, characterized in that: The steps of preparing Na-X zeolite by microwave hydrothermal synthesis method include: (1) dissolving Na2SiO3 and NaAlO2 in alkaline solutions respectively to prepare Na2SiO3 solutions and NaAlO2 solutions; (2) Na2SiO3 solution was added dropwise to NaAlO2 solution, and after microwave reaction at 85-95°C, the solid was separated to obtain Na-X zeolite.
5. The preparation method according to claim 1, characterized in that: Step (1) comprises: An aqueous solution containing an iron source, a nickel source and PEG is mixed with Na-X zeolite to prepare a first mixture; and an aqueous solution containing a reducing agent and concentrated hydrochloric acid is dripped into the first mixture under an inert atmosphere to prepare a fluorescent probe P1.
6. The preparation method according to claim 5, characterized in that: The inert atmosphere is N2.
7. A fluorescent probe, characterized in that It is prepared by the preparation method described in any one of claims 1 to 6.
8. A reagent or a kit, characterized in that: It contains the fluorescent probe according to claim 7.
9. Use of the fluorescent probe according to claim 7, or the reagent or kit according to claim 8 in the detection of cations and / or anions.
10. The use according to claim 9, characterized in that: The cation is Zn 2+ 、Al 3+ Mg 2+ At least one of; and / or, the anion is HPO4 2- .